Deeper Inside Finite-state Markov chains - Kien, Le Trung; Hieu, Le Trung; Hung, Tran Loc; Tien, Nguyen Duy (VNU Journal of Science: Mathematics - Physics; Vol 23 No 2, 2007)
A b s t r a c t . The eíĩective application o f Markov chains has been paid much attention, and it has raised a lot of thcoreticaỉ and applied problems. In this paper, vve vvould like to approach One o f these problems vvhich is íìnding the long-run behavior o f extremely huge-state Markov chains according to the direction of investigating the structure o f Markov Graph to reduce complexity o f computation. We focus on the vvay to access to the íìnite-state Markov chain theory via Graph theory. We suggested some basic knovvledge about State classiíìcation and a small project o f modelling the structure and the moving process of the /inite-state Aíarkov Chain modeỉ. This project based on the remark that il is impossible to study deeperly the finite-state Markov Chain theory i f vve do not have the clear sense about the structure and the movement o f it.